The Challenges of Constructing the Connectivity between Indonesia and Malaysia in the Malacca Strait - Awani Irewati (Journal of Indonesian Social Sciences and Humanities, 2020)
Today, people have lived in one integrated  space that make all their  needs and activities can be served quickly and they become interdependent . In line with that,  the implementation of connectivity concept within community, automatically, becomes inherent in their social and economic activities.Therefore, people need to construct connectivity in all activities. Even within the bigger community like ASEAN Community, people become more involved  in a cohesive and competitive situation in order to fulfill the desired goals. Referring to one of President Jokowi's maritime development programs, namely "Toll Laut", it is the Indonesia government's target to construct/ build up the potential regional zone as strategic hub that connects with its neighboring countries. The long-lived relationship between Indonesia and Malaysia in regards of the Malacca Strait has been articulated in numerous activities. This is in accordance with what the needs of coastal community of the two countries . In this case, Medan and Dumai of Sumatera Island in Indonesia are the two cities which have traditionally  established people to people connectivity with Penang  and Melaka cities of Malaysia. In the context of  ASEAN Community,  such a connectivity has been part of the ASEAN Community target. There are three elements inherent in the connectivity concept, namely infrastructures, institutions and people to people. The two Indonesia coastal regions in this regards need to construct the other two concepts of connectivity  in order to obtain the “normal” connectivity which is the prerequisite to connect Indonesia and Malaysia  in the Malacca Strait. This becomes a big challenge for the Indonesia to fulfill the target of competitive,cohesive and inclusive sub-regional connectivity development. This paper aims at scrutinizing the main quest, which focuses on the challenges faced by Indonesia in building up /constructing the maritime connectivity with Malaysia in the Malacca Strait. The paper  is in favor of the argument that the Indonesia’s maritime corridors [Dumai and Medan] seem to have problem. The maritime connectivity between the two countries has  not built adequately. In this regards, the government should streamline the management system linked to the internal connectivity issue.